Pengembangan Penilaian Kinerja Berbasis Outdoor Learning di SDN Sukabumi 6 Kota Probolinggo - Ryzca Siti Qomariyah; Errina Dinda Festawanti; Muthmainnah; Faradella Rahmadhini (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This observation is a development of performance assessment based on outdoor learning at SDN Sukabumi 6, Probolinggo City. This observation aims to 1) explain the implementation of performance appraisal in elementary schools, 2) explain the design of outdoor learning based performance assessment instruments, 3) implement the design of performance assessment instruments in outdoor learning based learning. This observation uses the Design Bases Research method. The development of this method itself consists of four stages, namely 1) identification and analysis of problems by researchers and practitioners collaboratively 2) developing solutions based on theoretical benchmarks, existing design principles and technological innovations 3) carrying out an iterative process to test and improve solutions practically 4 ) reflection to produce design principles and improve the practical implementation of solutions. Rubric is a scoring scale consisting of a series of achievement criteria and an explanation of the level of achievement in carrying out certain tasks. Rubrics can be used as assessment criteria about dimensions to decide student performance, a value scale to assess student performance. The results of the research are 1) outdoor learning-based performance assessment instruments; 2) validation by experts states that this performance appraisal instrument is feasible to use.